Precipitating Electron Energy Spectra and Auroral Power Estimation by Incoherent Scatter Radar With High Temporal Resolution. Issue 4 (5th April 2022) - Tesfaw, Habtamu W.; Virtanen, Ilkka I.; Aikio, Anita T.; Nel, Amoré; Kosch, Michael; Ogawa, Yasunobu
Abstract: This study presents an improved method to estimate differential energy flux, auroral power and field‐aligned current of electron precipitation from incoherent scatter radar data. The method is based on a newly developed data analysis technique that uses Bayesian filtering to fit altitude profiles of electron density, electron temperature, and ion temperature to observed incoherent scatter spectra with high time and range resolutions. The electron energy spectra are inverted from the electron density profiles. Previous high‐time resolution fits have relied on the raw electron density, which is calculated from the backscattered power assuming that the ion and electron temperatures are equal. The improved technique is applied to one auroral event measured by the EISCAT UHF radar and it is demonstrated that the effect of electron heating on electron energy spectra, auroral power, and upward field‐aligned current can be significant at times. Using the fitted electron densities instead of the raw ones may lead to wider electron energy spectra and auroral power up to 75% larger. The largest differences take place for precipitation that produces enhanced electron heating in the upper E region, and in this study correspond to fluxes of electrons with peak energies from 3 to 5 keV. Finally, the auroral power estimates are verified by comparison to the 427.8 nm auroral emission intensity, which shows good correlation. The improved method makes it possible to calculate unbiased estimates of electron energy spectra with high time resolution and thereby to study rapidly varying aurora. Key Points: We use the BAFIM‐ELSPEC analysis combination to calculate the energy spectra of precipitating electrons with high time resolution Using the fitted electron density data in precipitation events leads to wider energy spectra, and larger auroral power and field‐aligned current estimates Auroral power calculated using the BAFIM‐ELSPEC analysis correlates well with the 427.8 nm emission line intensity